2011
DOI: 10.1124/jpet.111.183665
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Basic Fibroblast Growth Factor Effect on Healing of Ulcerative Colitis in Rats

Abstract: We demonstrated previously that basic fibroblast growth factor (bFGF) accelerated the healing of experimental duodenal ulcers, and we now hypothesize that bFGF might also accelerate the healing of experimental ulcerative colitis (UC). We also explored the potential molecular mechanisms involved in the accelerated healing of UC in rats treated with bFGF. The results demonstrated that colonic lesions were significantly reduced by bFGF treatment, whereas neutralization of bFGF aggravated iodoacetamide-induced UC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…The assessment of hematological parameters can be used to determine the extent of disease state of colitis[13]. TNF-α, IL-1β, IL-6 and IL-8 like cytokines were released via the activation of white blood cells (including macrophages) via neutrophils[36]. This may have resulted in diarrhoea and malena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of hematological parameters can be used to determine the extent of disease state of colitis[13]. TNF-α, IL-1β, IL-6 and IL-8 like cytokines were released via the activation of white blood cells (including macrophages) via neutrophils[36]. This may have resulted in diarrhoea and malena.…”
Section: Discussionmentioning
confidence: 99%
“…The SOD content was determined as previously described by Misra and Fridovich[35] and SOD activity was expressed as U/mg protein. Glutathione (GSH) assay was performed according to the method of Moron et al (1979)[36] and the amount of reduced GSH was expressed as µg of GSH/mg protein. Myeloperoxidase (MPO) content was measured using the method of Krawisz et al (1984)[37] and MPO activity was defined as the quantity of enzyme degrading 1 µmol of peroxide per minute at 25°C and was expressed in units per gram (U/g) of wet scrapings.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that increased syndecan-1, TNF- α , and bFGF levels of patients with active IBD were declined after infliximab therapy [ 52 ]. In contrast, Paunovic et al [ 53 ] demonstrated that bFGF caused mucosal healing of ulcerative colitis in rat. Hepatocyte growth factor (HGF) is secreted from stromal cells present within the inflammatory tissue and activated by hepatocyte growth factor activator (HGFA).…”
Section: Angiogenic Mediatorsmentioning
confidence: 96%
“…For fibrosis, targeting collagen cross-linking enzymes (LOX family) is a new interesting issue [ 61 ]. Other natural antiangiogenic molecules studied for the therapy of IBD are Ang1 [ 40 ], TGF- β [ 50 ], bFGF [ 53 ], HGF [ 57 ], Cav-1 [ 72 ], and endoglin [ 11 ]. But use of these molecules needs more time and study.…”
Section: Antiangiogenic Therapies In Ibdmentioning
confidence: 99%
“…An intestinal fistulation study by Gao et al also found similar results [ 40 ]. Another study on ulcerative colitis induced with iodoacetamide found decreased bFGF levels in the first 6 h, which then increased until the 10th day of the study [ 41 ]. However, these results differ from those of a study on rat burn injury by Mansoub et al who found an increase in bFGF until the 7th day, followed by a decrease on the 14th day [ 30 ].…”
Section: Discussionmentioning
confidence: 99%